Position of posterior superior alveolar artery in relation to the maxillary sinus using cone beam computed tomography in Indian sub-population - Godil Aamir Zahid; Devadiga Trupti Jagannath; Supnekar Shraddha Chandrashekhar; Kazi Arshi Ilyas; Wadwan Sanaa Akhlaq; Dugal Ramandeep (EDP Sciences, 2021)
Purpose: To assess the location of posterior superior alveolar artery (PSAA) using CBCT in relevance to sinus lift procedure for implant placement. Patients and Methods: A retrospective study was conducted using the CBCT data of 500 patients (n = 500). Linear measurements were carried out to localize the medio-lateral and vertical position of posterior superior alveolar artery in postero-lateral wall of maxillary sinus and its proximity to the floor of maxillary sinus using CS 3D imaging 3.7.0 software program. The relative position of PSAA was determined as; (a) intra-osseous, (b) below the membrane and (c) outer-cortex of lateral sinus wall. The location of PSAA was assessed in molar region bilaterally by using following radiographic measurement; (1) distance between the lower border of posterior superior alveolar artery and alveolar crest, (2) height from the floor of maxillary sinus to alveolar crest and (3) distance from the posterior superior alveolar artery to medial wall of maxillary sinus. Results: The prevalence of the artery was observed in 99.4% of the sinuses and was mostly intraosseous (84.2%).The mean distance between the lower border of the artery and alveolar crest is significantly higher in males compared to females (P < 0.01). The distribution of artery location did not differ significantly across various age groups (P > 0.05). Discussion/Conclusion: The most common variant of PSAA was identified in the intra-osseous region and the mean distance of the vessel to crest of the residual ridge differs significantly with gender and not with age.